Does Technology Readiness and Acceptance Induce more Adoption of E-Government? Applying the UTAUT and TRI on an Indonesian Complaint-Based Application - Dhia Khalila Rinjany (Indonesian Association for Public Administration, 2020)
Most researches relating to the success of information and technology system application focus on two separate matters, namely technology readiness and technology acceptance. Both perspectives are used to observe how technology is adopted by users. However, very few studies test them both concurrently in a single research. This research, therefore, aims to conduct testing on the two concurrently without separating them. This article attempts to put two differing theories to the test, which are the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Readiness Index (TRI), in the context of e-government that is carried out via the Jakarta Smart City Program. To be more specific, the aJakarta Smart City Program analyzed in this study is the Qlue and CRM (Citizen Management Relationship) applications. The research method employed in this article is the quantitative method, wherein 225 respondents participated in this research to assess the level of technology readiness, the gathered data were subsequently processed by using the descriptive statistics analysis technique. Furthermore, 185 respondents also participated in observing how behavior influences the intention to use technology. These data were processed by using multiple linear regression analysis. Research results indicate that Jakarta SCR citizens’ technology readiness level can still be categorized as low and is identified as belonging to the Low Technology Readiness group, with a total TRI value of 2.7. Additionally, this research also shows that performance expectancy (PE), effort expectancy (EE), social influence (SI), and facilitating conditions (FC) have positive and significant influence on the dependent variable, namely the behavioral intention to use the system (BIUS).